2022
DOI: 10.3389/fpubh.2022.975413
|View full text |Cite
|
Sign up to set email alerts
|

Lead exposure is non-linearly associated with subclinical myocardial injury in the general population without cardiovascular disease

Abstract: Background and aimsGrowing studies have focused on the effect of lead exposure on human circulatory system, while the relationship between lead exposure and subclinical myocardial injury (SC-MI) is still poorly known. Therefore, this study was to explore the effect of lead exposure on SC-MI.MethodsThe study included 6,272 individuals aged 40 and older without cardiovascular disease (CVD) from the third National Health and Nutrition Examination Survey. Blood lead was used as an alternative marker of lead exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Findings from the general US population using NHANES data have reported associations between increasing blood lead and subclinical myocardial injury. 53 Various studies performed in occupationally exposed populations have also identified a variety of cardiovascular measures associated with blood lead, 10 including increased prevalence of LV hypertrophy, 54 higher left ventricular mass, and lower ejection fraction. 55 Previous findings from the SHFS identified the association of higher urinary arsenic levels with higher levels of LV wall thickness and LV hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from the general US population using NHANES data have reported associations between increasing blood lead and subclinical myocardial injury. 53 Various studies performed in occupationally exposed populations have also identified a variety of cardiovascular measures associated with blood lead, 10 including increased prevalence of LV hypertrophy, 54 higher left ventricular mass, and lower ejection fraction. 55 Previous findings from the SHFS identified the association of higher urinary arsenic levels with higher levels of LV wall thickness and LV hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“… 48 A recent study found a positive correlation between the risk of subclinical myocardial injury, assessed with a 12-lead electrocardiogram-based cardiac infarction/injury score, and BLLs higher than 3.8 ug/dL. 49 A Mexican study also reported a significant association between lead exposure and an increase in body mass index, with BLLs averaging 0.051 ± 0.035 μg/dL, 0.107 ± 0.067 μg/dL, and 0.151 ± 0.063 μg/dL in individuals with normal weight, overweight, and obesity, respectively. 50 Supplemental Table 3 summarizes the major studies on the association between lead and CVD.…”
Section: Air Pollutionmentioning
confidence: 99%
“…Molecules 2023, 27, x FOR PEER REVIEW 2 of 39 damage to the mucosa of the gastrointestinal tract and proximal renal tubules, which manifests clinically as abdominal pain, hemorrhagic gastroenteritis, acute tubular necrosis, and subacute shock [10,11]. The pathophysiological toxicity of lead (Pb) is fairly complicated as it involves almost every organ system, with the most severe neurological manifestations being seizures and coma [12][13][14]. Cadmium (Cd) can disrupt iron homeostasis in humans by inducing hyperactivation of heme oxygenase-1 (HO-1) and disrupting lipid metabolism, which ultimately leads to iron apoptosis [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%